Regional development and conflict management a case for Brazil - Bar-El, Raphael (Contributions to conflict management, peace economics and development ;, 2008)
This book is about the courageous decision taken by the Government of a Ceara, Brazil, to tackle the painful economic and social conflict caused by the enormous gap between rich and poor. Instead of confining their attempts to easy solutions like transfer payments, the Governor of the State, Tasso Ribeiro Jereissati, decided in 2001 to cut straight into the roots of the problem, aiming to develop a genuine understanding of the conflict between growth and distribution, and thereby provide real, long-term solutions to the state's problems. Pedro Sisnando Leite, then Secretary of Rural Development, led this effort together with other state secretaries, particularly Monica Clark Nunes Cavalcante, Carlos Matos Lima and Alex Araujo.The book presents the results of a unique harmonic integration between academic research, public policy elaboration, and concrete implementation of public measures. The policies devised, implemented and evaluated in this book are focused on potential solutions to this market failure, at both the regional level and the local level. Studied and endorsed by many academics and policy makers around the world, the model of Ceara provides a unique and exemplary solution to conflict and inequality.